Efisiensi termal dan efektivitas produksi kondensor pada solar still terpadu - Dan Mugisidi; Adittia Fajar; Rifky Rifky; Oktarina Heriyani (Jurnal Teknosains, 2022)
Water is a basic human need that must be fulfilled. The need for clean water is increasing while the availability of clean water is limited, so researchers are trying to use sea water as raw material for fresh water. Sea water is an abundant source of water but still contains salt, therefore it is necessary to separate sea water and its salt content to produce fresh water or desalination, one way is to use solar stil. Solar stills are mostly used for desalination processes on the coast and remote area because they can be operated easily and can be manufactured at low cost. However, solar still has low productivity, so various studies have been carried out to increase desalination yields, such as the addition of a condenser. Aim of this study was to determine the thermal efficiency and effectiveness of the condenser on solar stills. The research was conducted in period March - May 2021. The materials used are aluminum with a length of 300 mm, a width of 300 mm and a thickness of 1.6 mm for the basin plate, double glass with a thickness of 3 mm for the top and sides of the solar still. The study was conducted indoor with radiation intensity using halogen lamps. The variables measured were water temperature, evaporation, inner glass surface, condenser, inlet and outlet of the condenser cooler using a fluke meter, radiation intensity using a solar power meter and desalinated water using a digital balance. From the results of the study, the average thermal efficiency of the condenser in the integrated solar still reached 83.94% and the desalination mass of seawater reached 451.32 grams with the effectiveness of condenser production of 96.4% and the correlation value of 0.99.